Modelling and simulation of hybrid technology in vehicles - Abrar Ahmed; Palaksh Yelamali; R. Udayakumar (Energy Reports, 2020)
This study focuses on the performance results obtained from comparing two variants of naturally aspirated petrol engines to a petrol engine with hybrid electric assist using MATLAB Driveline. The comparative study analyses the power output obtained from the simulations. The new era of hybrid electric technology can provide performance comparable to naturally aspirated engines is the main focus of this paper.
Keywords: 330; ERS - Energy Recovery System; MGU-K - Motor Generator Unit- Kinetic; MGU-H - Motor Generator Unit- Heat; KERS - Kinetic Energy Recovery System; ES - Energy Store